Rekonstruksi Pengawasan DPR RI dalam Pembentukan Peraturan Perundang-undangan melalui Kerangka Demokrasi Konstitusional - Silalahi, Artha Debora (UI Scholars Hub, 2023)
The process of forming laws and regulations often ignores the rights of citizens, especially the citizen participation rights, the supervision of the House of Representatives and the involvement of citizens. Many problems still unable to accommodate the aspirations of the community, minimize the civil space and only limited to the elite, resulting in discrepancies and ambiguity of implementing the regulations are not simultaneous. Through this paper, using the juridical-normative method with a conceptual approach wants to review the kinds of the reconstruction of the House of Representatives supervision through the bargaining position process as a political aspiration line and citizen participation rights as a tool of legal communication during the formation of laws and regulations in constitutional democracy framework. The reconstruction form of the House of Representatives supervision through the bargaining position process can be divided into two are preventive supervision carried out when the legal product still processing in the draft legislation and repressive supervision carried out when legal product has been formed.